Nieskończona pieśń o człowieku. O Wiesławie Wodnickim - Niezgoda, Grażyna (Wydział Sztuki UR, 2017)
Wiesław Tadeusz Wodnicki’s paintings used to dominate in group exhibitions – with their colors, large formats, flourish, expression. Using so intense means of expression, he conveyed lyrical and personal messages. A loner, he was very active exhibiting his works. Faced with the choice between line versus color, he chose both. The artist’s life revolved around art. He painted a lot, took active part in artistic life, was a member of many artist groups. His life was connected with Przemyśl and Jarosław, which were his home and a frequent theme of his work. It was very early that he developed his own artistic language, his style, which can be regarded as part of the figurative trend. The focus of his work was man and figurative compositions were the most important theme he took up. They were arranged in series and one of them was called Nieskończona pieśń o człowieku (Unfinished song about man).
Unfinished song about man
Keywords: autoportret; czas; ekspresja; styl; kolor; selfportrait; time; expression; style; colour